Penggunaan Modal Verbs Bahasa Inggris dalam Ketrampilan Berbicara - Maria Theresia Priyastuti (Journal of Language and Health, 2020)
This research discusses the form of modality and the meaning of modality in English learning process using role play method. This research discusses the form of modality and the meaning of modality in English learning process using role play method. Objective to describe the form of modality and to explain the meaning of modality. The form of modality that is used in speaking is deontic modality with the modal verbs such as “must, has to atau have to, should, can/could” and the meanings of modality which are found, are order/necessity modality and permission modality. Descriptive qualitative with equal pragmatic methods. The data were taken from the conversation of role play which contained modal verbs. The sampling of the research were used randomly when the nursing students did role play of giving health education with diet program theme. firstly, the main form of modality in the conversation of role play using modal verb “can and will”. Secondly the meaning of modality which is often found in conversation of role play is deontic modality for asking permission. The nursing students are able to use English modal verbs correctly in role play learning process.